1989
DOI: 10.1210/jcem-68-5-873
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response Study and Long Term Effect of the Somatostatin Analog Octreotide in Patients with Therapy-Resistant Acromegaly*

Abstract: Twelve acromegalic patients in whom standard therapy was unsuccessful were evaluated with 24-h serum GH profiles (hourly sampling) and oral glucose tests (oGTT) while being treated with octreotide, a long-acting somatostatin analog. During a dose-response study (300, 600, and 1500 micrograms/day sc, for 4 weeks), serum GH decreased significantly after 300 micrograms/day in 8 of 12 patients [from 14.5 +/- 6.2 (+/- SE) to 4.9 +/- 1.9 micrograms/L]. Higher doses further reduced serum GH concentrations in 3 (600 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
26
1

Year Published

1991
1991
1998
1998

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 25 publications
8
26
1
Order By: Relevance
“…In this study, the plasma insulin responses to an oral glucose load in 4 patients with GIT (cases 3, 4, 5 and 6) were lowered after the octreotide therapy, in accordance with previous reports [9,10]. However, the responses to an oral glucose load in 2 patients with NGT (cases 1 and 2) increased after the octreotide administration in accordance with the observation of Ken et ai.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, the plasma insulin responses to an oral glucose load in 4 patients with GIT (cases 3, 4, 5 and 6) were lowered after the octreotide therapy, in accordance with previous reports [9,10]. However, the responses to an oral glucose load in 2 patients with NGT (cases 1 and 2) increased after the octreotide administration in accordance with the observation of Ken et ai.…”
Section: Resultssupporting
confidence: 92%
“…Chiba reported that the effects of somatostatin on insulin were different with differing levels of glucose and glucagon [16]. Our observations and these previous reports [9,10,12,16] indicate that the effects of octreotide, a somatostatin analogue, as well as somatostatin itself on insulin secretion may vary according to the severity of glucose intolerance.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…The somatostatin analog octreotide is used for longterm treatment of acromegalic patients in whom previous therapy has failed to normalize serum growth hormone (GH) concentration (1,2). More recently, it has also been used for preoperative suppression of GH secretion and reduction of tumor size (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%